Content Analysis: Language Skills Comparison on the KTSP and K-13 English Textbooks - Khusna, Febriana Aminatul (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
Education is one of the main focuses in every country. The better the quality of education in a country, the easier it will be to improve and build the quality of the country in various fields. The status of English language in Indonesia is a foreign language. This condition causes many Indonesian people still having difficulty in learning and using it. Using textbooks is one of the alternative in delivering material. However, the textbook used must be made in accordance with the applicable curriculum. Each curriculum has its main focus respectively in learning. The purpose of this study is to interrogate and compare the main focus in language skills that are applied in English language textbooks. “Developing English Competence for SMA/MA grade XII (KTSP)” with “Bahasa Inggris Edisi Revisi 2018 SMA/MA/SMK/MA/MAK Kelas XII” are used in this research. Descriptive qualitative research with content analysis method is used in this research to get the best data.